Screen media and its impact on children - Nima, Malayamparambathu; Jithesh, Madhavan (International Research Journal of Ayurveda & Yoga, 2020)
Screen media includes any media that is produced for or distributed via the screen, including television, computer, tab, smart phone etc. Due to the inadequacy of time and the increasing workload, parents resort to gadgets and smart screen to engage their children. Studies suggest that maximum brain development occurs by the age of seven and the content, children see or hear at this age will shape their entire future. Screen media play an imperative role in influencing the developmental stages of a child. Both positive as well as negative role can be attributed to any advancements in technology including, the screen media. Excess use of gadgets especially in children may direct to screen addiction that leads to impaired daily functioning in terms of productivity, social relationships as well as emotional wellbeing. Screen addiction management strategies are bidirectional which includes providing psycho education to the parent and also advising behavioral modification for the child. Here the pros and cons of screen media, screen addiction and also the selected aspects of management with special reference to the Ayurvedic approach are being highlighted.